If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + (x + 60) + (3x + -30) = 180 Reorder the terms: 2x + (60 + x) + (3x + -30) = 180 Remove parenthesis around (60 + x) 2x + 60 + x + (3x + -30) = 180 Reorder the terms: 2x + 60 + x + (-30 + 3x) = 180 Remove parenthesis around (-30 + 3x) 2x + 60 + x + -30 + 3x = 180 Reorder the terms: 60 + -30 + 2x + x + 3x = 180 Combine like terms: 60 + -30 = 30 30 + 2x + x + 3x = 180 Combine like terms: 2x + x = 3x 30 + 3x + 3x = 180 Combine like terms: 3x + 3x = 6x 30 + 6x = 180 Solving 30 + 6x = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-30' to each side of the equation. 30 + -30 + 6x = 180 + -30 Combine like terms: 30 + -30 = 0 0 + 6x = 180 + -30 6x = 180 + -30 Combine like terms: 180 + -30 = 150 6x = 150 Divide each side by '6'. x = 25 Simplifying x = 25
| 0.6g+11=-5 | | X/a-1= | | 7.8/7.41 | | 5a+(2a-5)-(a-3)=16 | | 7(4y-9)-(4y+8)= | | b^2-7b-36=0 | | (e-b)(c-d)= | | 21-6x=9 | | -243^(3/5) | | 3y-1+2x-4+x+3+15= | | 8x+46=5(x+5) | | 3n-4l= | | 6x^2=15 | | 6.1x-1.5=10.7 | | 2x+4=12+x | | (3^√7y^5)/(3^√64x^6) | | 6(4z-1)-5(z+3)=12(z+1) | | 4+7(x-1)=4-9(x-5) | | 9z-5=16+6z | | (y^2+4)=2y^2-y-10 | | 4*(2x-3)=5(x+2) | | v=(1/3)pir^2h | | 3n-17=-19+4n | | -8*(8-1)=-16 | | x^2+6*x-3600=0 | | 1.5m+1.0m=7.5 | | 0=4(x^2+49)(x^2-36)(x-7) | | 1/5n=3.1 | | 18=3z+17 | | 35=8m+15 | | -16x+5= | | h-5=16 |